1973
DOI: 10.1111/j.1529-8817.1973.tb04077.x
|View full text |Cite
|
Sign up to set email alerts
|

A DESCRIPTION OF HAPLOZOON AXIOTHELLAE N. SP., AN ENDOSYMBIONT OF THE POLYCHAETE AXIOTHELLA RUBROCINCTA12

Abstract: SUMMARY A new parasitic dinoflagellate, Haplozoon axiothellae sp. nov., is described from the intestine of the marine polychaete Axiothella rubrocincta. The parasites are 40–175 μm long with 2–26 cells arranged in single or double rows. Two cytoplasmic inclusions previously unknown in this genus are described. The first is globular and varies in size, while the second is approximately 2 μm long and peanut‐shaped. The function and composition of the inclusions are unknown. Nuclear structure and karyokinesis are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 6 publications
1
17
1
Order By: Relevance
“…The pseudocolonial cell organization of Polykrikos species is among the most novel features of these dinoflagellates. A similar cellular organization has also been described for parasitic dinoflagellates, such as Haplozoon Dogiel, where, for example, H. axiothellae Siebert forms a compartmentalized syncytium (Siebert 1973, Siebert and West 1974, Leander et al 2002). The compartments in the pseudocolonies of H. axiothellae each contain at least one nucleus, are partitioned by alveolar membranes, and are enveloped by a continuous plasma membrane.…”
mentioning
confidence: 58%
“…The pseudocolonial cell organization of Polykrikos species is among the most novel features of these dinoflagellates. A similar cellular organization has also been described for parasitic dinoflagellates, such as Haplozoon Dogiel, where, for example, H. axiothellae Siebert forms a compartmentalized syncytium (Siebert 1973, Siebert and West 1974, Leander et al 2002). The compartments in the pseudocolonies of H. axiothellae each contain at least one nucleus, are partitioned by alveolar membranes, and are enveloped by a continuous plasma membrane.…”
mentioning
confidence: 58%
“…The posteriormost surface of each trophocyte was distinctly smooth and identified as the "neck", where the dorsal region of the neck was much broader (7-11 µm at maximum breadth) than the ventral region (Figs 1, 2a-c). We infer that the neck region contains the nucleus of the trophocyte as TEM data demonstrated that the nucleus is located in the posterior third of each trophocyte (Siebert 1973;Siebert and West 1974).…”
Section: General Morphologymentioning
confidence: 69%
“…Accordingly, we have examined the surface morphology of thirteen different individuals of H. axiothellae using scanning electron microscopy (SEM) to complement the two original papers describing H. axiothellae with TEM (Siebert 1973;Siebert and West 1974). We not only report new findings on the structures noted above, but we provide evidence for what we suspect are unusual episymbionts and evidence which indicates that each individual parasite is surrounded by a single membrane.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Myxodinium pipiens is presumably restricted to the chlorophyte genus Halosphaera, yet this parasite is only known from one study of Mediterranean plankton. Similarly, the 10 species of Haplozoon most of which have been reported only once, are believed to be highly host specific, with each infecting a single host species (Shumway 1924;Siebert 1973).…”
Section: Photomentioning
confidence: 99%